2015
DOI: 10.1002/erv.2353
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Intensive Family Therapy for Adolescent Eating Disorders: 30‐Month Outcome

Abstract: Family therapy approaches have generated impressive empirical evidence in the treatment of adolescent eating disorders (EDs). However, the paucity of specialist treatment providers limits treatment uptake; therefore, our group developed the intensive family therapy (IFT)-a 5-day treatment based on the principles of family-based therapy for EDs. We retrospectively examined the long-term efficacy of IFT in both single-family (S-IFT) and multi-family (M-IFT) settings evaluating 74 eating disordered adolescents wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 42 publications
0
61
0
Order By: Relevance
“…A retrospective study [64], which compared MFT plus treatment as usual (TAU) to a matched control group receiving only TAU, found that both cases and controls experienced significant weight restoration, but the addition of MFT led to quicker weight gain and higher rates of full weight restoration. Another retrospective study carried out within the framework of an intensive therapeutic program in San Diego [26,65] MFT treatments with a psychoeducational orientation have generated only one comparative study. In a small RCT involving AN adolescent inpatients, Geist et al [32] compared 8 sessions of individual family therapy (FT) with 8 sessions of family group psychoeducation (FGP) over a 4-month study period and found that both treatment modalities equally supported weight restoration, the preference being once more given to FGP because of its better cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study [64], which compared MFT plus treatment as usual (TAU) to a matched control group receiving only TAU, found that both cases and controls experienced significant weight restoration, but the addition of MFT led to quicker weight gain and higher rates of full weight restoration. Another retrospective study carried out within the framework of an intensive therapeutic program in San Diego [26,65] MFT treatments with a psychoeducational orientation have generated only one comparative study. In a small RCT involving AN adolescent inpatients, Geist et al [32] compared 8 sessions of individual family therapy (FT) with 8 sessions of family group psychoeducation (FGP) over a 4-month study period and found that both treatment modalities equally supported weight restoration, the preference being once more given to FGP because of its better cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…85 Marzola et al followed up 54 adolescents, 30 months after a brief intensive MFT intervention, reporting 59.3% remission (>95% expected body weight [EBW]) rates and a further 27.7% partial remission (>85% EBW). 86 MFT-AN is a highly acceptable intervention to families, with more than 90% completing the treatment, with significant improvement in weight and other patient symptoms, improvements in parents' mood and better family relationships. 87,88 Pharmacological treatment -efficacy of antidepressants and atypical antipsychotics NICE does not support medication as a primary or only treatment for AN.…”
Section: Multiple Family Therapy (Mft)mentioning
confidence: 99%
“…Other components include daily parent-only and patient-only group sessions, and individual family psychiatric and medical evaluations. Multi-family intensive family treatment (IFT) is deemed suitable by families and has demonstrated preliminary efficacy for patients with a broad range of ages (8-27), eating disorder diagnoses (Marzola et al, 2015;Rockwell et al, 2011), and phases of treatment. This heterogeneous group composition serves a number of diverse patient needs including supporting transitions between phases of treatment or levels of care, augmenting traditional individual therapy, and as a booster for patients failing to make gains in outpatient care.…”
Section: Program Descriptionmentioning
confidence: 99%
“…In response to these barriers, recent endeavors by our group have sought to establish short-term intensive treatment programs, which allow temporary immersion into otherwise inaccessible evidence-based treatment programs, with preliminary reports suggesting promising findings (Marzola et al, 2015;Rockwell, Boutelle, Trunko, Jacobs, & Kaye, 2011). Initially, these short-term intensive treatments were developed for individual families (Rockwell et al, 2011), although recently have evolved into a more costeffective multi-family format (Marzola et al, 2015), demonstrating promising outcomes comparable to both outpatient FT-AN (Lock & Le Grange, 2012) and intensive family therapy for individual families (Rockwell et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation